Fluorine-free halogen-free flame-retardant PA6 material as well as preparation method and application thereof
By using a phosphorus-based bridge agent containing benzene ring and carboxyl group in the PA6 material for cross-linking reaction with a polyvinyl alcohol cross-linking agent, the problem of easy dripping of PA6 material and large amount of halogen-free flame retardant added during combustion is solved, and a fluorine-free, halogen-free flame retardant PA6 material with high flame retardant grade and excellent mechanical properties is achieved.
Patent Information
- Application Number
- CN202411709175.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, PA6 materials are prone to dripping during combustion, and halogen-free flame retardant requires a large amount of added and fluorine-containing anti-dripping agent, which poses problems of environmental protection risks and high cost.
By crosslinking with a phosphorus-based bridge agent containing benzene ring and carboxyl group, a stable crosslinking product is formed, replacing the traditional fluorine-containing anti-drip agent, and improving the flame retardant grade and mechanical properties of PA6 materials.
The flame-retardant PA6 material without fluorine, halogen, has good flame retardant grade (such as V0) and excellent mechanical properties, while avoiding PFAS environmental risks and reducing material preparation costs.
Smart Images

Figure BDA0005155232930000051 
Figure FDA0005155232920000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a fluorine-free and halogen-free flame-retardant PA6 material and a preparation method and application thereof. Background Art
[0002] Nylon 6 (PA6) is an engineering plastic with excellent comprehensive properties and is widely used in various fields. It has high mechanical strength, good wear resistance, chemical resistance and electrical insulation. However, PA6 itself has certain flammability, its limiting oxygen index (LOI) is low, it is easy to burn and may produce dripping during the combustion process, which limits its application in some fields that have special requirements for flame retardant properties. Therefore, the flame retardant modification technology of PA6 has become a hot research topic.
[0003] Halogen flame retardant modification has been widely used in PA6 flame retardant modification due to its good flame retardant effect and low cost. However, due to the possibility of generating toxic gases and corrosive substances during the combustion process, which may cause harm to the environment and human health, some countries and regions have begun to restrict or prohibit the use of some halogen flame retardants. Halogen-free flame retardant promotes the formation of carbon layer in the condensed phase, blocks oxygen and heat transfer, and releases non-combustible gas in the gas phase to dilute the concentration of combustible gas. It has the advantages of low smoke, low toxicity, good heat resistance, etc., which is more in line with modern environmental protection and safety requirements. However, halogen-free flame retardants may require a large addition amount and the addition of fluorine-containing anti-dripping agents to achieve the ideal flame retardant effect. These cost factors and environmental factors will affect its competitiveness and wide application in the market.
[0004] Related technology discloses that the anti-drip performance of the material is improved by reacting butyl acrylate, methyl methacrylate and 2-bromoacrylic acid in a polytetrafluoroethylene dispersion to form a bromine complex polymer. Although this anti-drip strategy is effective, it still contains halogen and halogen, and a large amount of smoke will be generated during the combustion process, and the environmental protection performance needs to be improved.
[0005] The related technology discloses the use of 5.0-8.0% of polyhydroxy-substituted aromatic Schiff base and 12.0-15.0% of high-polymerization degree ammonium polyphosphate for compounding, so that nylon 6 passes the UL94V-0@3.2mm flame retardant rating and resists dripping. However, this solution requires the addition of a large amount of flame retardant to achieve the flame retardant effect. Summary of the invention
[0006] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the purpose of the present invention is to provide a fluorine-free and halogen-free flame-retardant PA6 material and a preparation method and application thereof, aiming to improve the flame retardant grade and / or strong mechanical properties of the PA6 material.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The first aspect of the present invention provides a fluorine-free and halogen-free flame-retardant PA6 material, whose raw materials include, by weight, 400-800 parts of nylon 6 resin, 10-100 parts of toughening agent, 30-300 parts of halogen-free flame retardant, 10-60 parts of phosphorus-based bridging agent containing benzene ring and carboxyl group, 5-15 parts of polyvinyl alcohol, 3-15 parts of other additives, and 200-400 parts of glass fiber.
[0009] Different from the traditional anti-dripping agent containing fluorine, the present invention uses a phosphorus-based bridging agent containing benzene rings and carboxyl groups and a polyvinyl alcohol cross-linking agent to undergo a cross-linking reaction during combustion. The phosphorus-based bridging agent containing benzene rings and carboxyl groups is stably and evenly fixed on the polymer surface through the cross-linking agent, and the charring effect is uniform, thereby promoting the flame retardant effect; at the same time, during the processing of the polyvinyl alcohol cross-linking agent, the hydroxyl group will be dehydrated to form a double bond structure on the end of the main chain of the molecule. The double bond structure can not only undergo thermal cross-linking, but also form a rigid and stable aromatic condensed ring structure with the benzene ring structure in the phosphorus-based bridging agent, thereby improving the charring effect of nylon 6 during combustion and also improving the melt viscosity during combustion, avoiding dripping of PA6 during combustion and making it have a better flame retardant grade (such as V0), solving the problem that the halogen-free flame retardant PA6 in the prior art causes the PFAS environmental risk due to the addition of polytetrafluoroethylene (PTFE) anti-dripping agent, but the problem that the thin-wall flame retardant grade does not meet the standard if PTFE is not added.
[0010] Those skilled in the art know that, within a certain range, the greater the amount of flame retardant added, the higher the flame retardant grade of the resin. However, in the technical solution of the present invention, even when the amount of flame retardant added is small, the nylon 6 material has a good flame retardant grade (such as V1, V2) while having excellent flow properties and mechanical properties.
[0011] On the other hand, in the present invention, the carboxyl group in the phosphorus-based bridging agent and the hydroxyl group of polyvinyl alcohol undergo an incomplete esterification reaction during the processing. The phosphorus-based bridging agent acts as a molecular anchor point to fix the molecular chain segment of PVA by means of chain segment entanglement, effectively improving the molecular internal energy of the nylon 6 material. At the same time, the hydrogen bonding between the hydroxyl group in PVA and the amide group in nylon 6 further enhances the mechanical properties of the material. By adding a phosphorus-containing bridging agent and a cross-linking agent, the mechanical properties of the nylon 6 material have been significantly improved, which is not only due to the fixing effect of the molecular anchor point, but also due to the synergistic enhancement effect of the hydrogen bonding effect.
[0012] In some embodiments of the present invention, the fluorine-free and halogen-free flame-retardant PA6 material, in parts by weight, comprises raw materials including 400-800 parts of nylon 6 resin, 10-50 parts of toughening agent, 90-250 parts of halogen-free flame retardant, 10-50 parts of phosphorus-based bridging agent containing benzene ring and carboxyl group, 5-30 parts of polyvinyl alcohol, 3-10 parts of other additives, and 200-400 parts of glass fiber.
[0013] In some embodiments of the present invention, the relative viscosity of the nylon 6 resin measured in a 0.01 g / mL concentrated sulfuric acid solution at 25° C. is 2.2 to 2.6 Pa·S, such as 2.4 Pa·S.
[0014] In some embodiments of the present invention, the polyvinyl alcohol is polyvinyl alcohol 1799, whose structural formula is The molecular weight is 70000-80000, the alcoholysis degree is 99%, and n is 1600-1800.
[0015] In some embodiments of the present invention, the phosphorus-based bridging agent containing a benzene ring and a carboxyl group includes at least one of bis(4-carboxyphenyl)phenylphosphine oxide, hexa-p-carboxylphenoxy cyclotriphosphazene (HCPCP), [(6-oxo-6H-dibenzo[c,e][1,2]oxaphosphorin-6-yl)methyl]succinic acid (DDP), 26-oxo-6H-dibenzo(c,e)(1,2)oxaphosphorin-6-one-succinic acid (DOPOMA) or [(6-oxo-6H-dibenzo[c,e][1,2]oxaphosphorin-6-yl)methyl]succinic anhydride (DMSA), 2-carboxyethylphenylphosphinic acid (CEPPA), and phenyldicarboxyphenylphosphine oxide (BCPPO). When the melting temperature of the phosphorus-based bridging agent containing a benzene ring and a carboxyl group (such as DDP) is close to the melting temperature of nylon 6 resin, the viscosity of the system can be significantly reduced during processing, thereby improving the fluidity of the material.
[0016] In the present invention, taking DPP as an example, its structural formula is With polyvinyl alcohol 1799 After cross-linking, the following products are formed: Wherein R1, R2, R3, R4 can be [C2H4O] m The repeating unit is composed of 1, wherein m is 1 to 1800.
[0017] In some embodiments of the present invention, the toughening agent includes methyl methacrylate-butadiene-styrene terpolymer and / or high rubber powder.
[0018] In some embodiments of the present invention, the halogen-free flame retardant includes aluminum hypophosphite (AHP) and / or diethyl aluminum hypophosphite; preferably, the halogen-free flame retardant includes aluminum hypophosphite and diethyl aluminum hypophosphite in a weight ratio of 0.5 to 2:1.
[0019] In some embodiments of the present invention, the other additives include antioxidants and / or lubricants, the antioxidants and lubricants are composed of a weight ratio of 1:1 to 3, the antioxidants include hindered phenol antioxidants and phosphite antioxidants, and the lubricants include fatty amide lubricants. Preferably, the hindered phenol antioxidants and phosphite antioxidants are compounded with the lubricant in a weight ratio of 1:1:2.
[0020] In some embodiments of the present invention, the hindered phenol antioxidant includes N,N'-1,6-hexylene-bis-[3,5-di-tert-butyl-4-hydroxyphenylpropionamide], and the phosphite antioxidant includes (2,4-di-tert-butylphenyl) phosphite triester.
[0021] In some embodiments of the present invention, the lubricant comprises silicone powder.
[0022] The second aspect of the present invention provides a method for preparing the fluorine-free and halogen-free flame-retardant PA6 material, comprising the following steps: weighing the raw materials, stirring and mixing them at high speed, extruding and granulating, and cooling to obtain the fluorine-free and halogen-free flame-retardant PA6 material.
[0023] In some embodiments of the present invention, the stirring rate of the high-speed stirring is 400 rpm-800 rpm and the time is 4 to 6 minutes.
[0024] In some embodiments of the present invention, the extrusion is carried out in a twin-screw extruder; the extrusion temperature is 220-240° C., and the screw speed is 260-310 rpm.
[0025] In some embodiments of the present invention, the preparation method further comprises drying the nylon 6 and polyvinyl alcohol crosslinking agent before the raw materials are stirred and mixed at high speed, and the drying temperature is 60 to 85° C. and the drying time is 3 to 5 hours.
[0026] The third aspect of the present invention proposes an application of the fluorine-free and halogen-free flame-retardant PA6 material in the office chair, home appliance, automobile or power tool industries.
[0027] The beneficial effects of the present invention are:
[0028] The present invention uses a cross-linked product formed by blending a phosphorus-based bridging agent containing a benzene ring and a carboxyl group with PVA to replace the traditional fluorine-containing anti-drip agent polytetrafluoroethylene, thereby eliminating the environmental risk of PFAS and preparing a more environmentally friendly flame retardant material;
[0029] The present invention selects a phosphorus-based bridging agent containing a benzene ring and a carboxyl group and a composite cross-linked PVA as an anti-dripping agent. The phosphorus-based bridging agent containing a benzene ring and a carboxyl group as a phosphine oxide substance has a certain flame retardant effect, which can reduce the use of phosphorus-based flame retardants and reduce the preparation cost of materials.
[0030] PVA is connected with the phosphorus-based bridging agent containing benzene rings and carboxyl groups through an esterification reaction, which increases the entanglement of polyvinyl alcohol in the nylon 6 matrix. It not only makes the phosphorus-based bridging agent containing benzene rings and carboxyl groups have a good dispersion effect in the nylon 6 matrix, but also forms carbon uniformly during the combustion process, thereby making nylon 6 have a good flame retardant effect, solving the problem that V0 level cannot be achieved without adding anti-dripping agent in the case of thin walls.
[0031] PVA will destroy the crystal area of nylon 6, reduce the melting temperature of nylon 6, and improve the processing fluidity of the material. However, due to the hydrogen bonding effect between the amide bonds of PVA and nylon, the interaction force between the molecular chains is enhanced, thereby improving the mechanical properties of the material.
[0032] The modified material has excellent mechanical properties and flame retardant effect, which reflects unexpected effects. At the same time, the preparation method of the present invention is simple, the process operation is easy to implement, and the prepared PA6 material can meet the requirements of home appliances, automobiles, and electronic and electrical industries for product safety. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0034] Examples and Comparative Examples
[0035] Examples 1 to 7 and comparative examples 1 to 6 were prepared from the raw materials shown in Table 1, wherein PA6 was M2400 from Xinhui Meida; aluminum hypophosphite and diethyl aluminum hypophosphite were from Qingyuan Pusai Fufos Chemical Co., Ltd.; DDP was from Xijia New Materials Co., Ltd.; PVA1799 was from Aladdin Reagent; the antioxidant was obtained by combining N,N'-1,6-hexylene-bis-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide) and tris(2,4-di-tert-butylphenyl) triester in a weight ratio of 1:1; and the glass fiber was 995-13C from Owens Corning.
[0036] Table 1
[0037]
[0038] The preparation method of fluorine-free and halogen-free flame-retardant PA6 material comprises the following steps:
[0039] 1) Dry PA6 resin and PVA1799 at 80°C for more than 4 hours;
[0040] 2) Weigh the raw materials according to the formula and mix them in a high-speed mixer at 400 rpm-800 rpm for 4-6 minutes;
[0041] 3) The material after step 2) is added into a twin-screw extruder for extrusion granulation, and then pelletized after water cooling to obtain a fluorine-free and halogen-free flame-retardant PA6 material, wherein the temperature of each zone of the twin-screw extruder is 220-230° C., and the speed of the screw is 260-310 rpm.
[0042] Test example
[0043] The obtained fluorine-free and halogen-free flame-retardant PA6 material was injection molded into standard test specimens. The process conditions of injection molding were: nozzle temperature 230°C, temperatures of each zone 230°C, 250°C and 220°C, holding time 3-6s, injection pressure 30-60MPa. The test specimens were tested for performance, and the test results are shown in Table 2.
[0044] The present invention is tested using the following test methods:
[0045] Tensile strength: tested according to ASTM D638 standard;
[0046] Bending strength: tested according to ASTM D790 standard;
[0047] Notched impact strength: tested according to ASTM D256 standard;
[0048] Flame retardant performance: tested in accordance with UL 94 standard;
[0049] Glass fiber content: tested according to ASTM D2584 standard.
[0050] Table 2
[0051] Group Tensile strength(MPa) Bending strength(MPa) Notched impact (J / M) Flame retardant performance (1.5mm) Example 1 156 173 93 V2, dripping burning cotton Example 2 151 159 85 V2, dripping burning cotton Example 3 144 155 90 V1, dripping non-flammable cotton Example 4 134 159 86 V0, 41s Example 5 136 163 89 V0, 26s Example 6 176 213 105 V0, 15s Example 7 114 134 72 V0, 27s Comparative Example 1 122 144 76 V2, dripping burning cotton Comparative Example 2 119 134 71 V0, 39s Comparative Example 3 118 128 68 V2, dripping burning cotton Comparative Example 4 139 163 87 V0, 45s Comparative Example 5 133 154 82 V0, 45s Comparative Example 6 112 128 76 V1, dripping non-flammable cotton
[0052] It can be seen from the mechanical properties table in Table 2 that in the present invention, the addition of phosphorus-containing bridging agent and cross-linking agent can appropriately improve the tensile strength, bending strength and impact strength, which may be attributed to the cross-linking of the cross-linking agent and the phosphorus-containing bridging agent, which increases the cross-linking degree of the molecular chain segments in the matrix, increases the interaction between the molecular chain segments, and reduces the fluidity of the molecular chain segments. However, if the amount of cross-linking agent added is too large, the crystallinity of the resin may be destroyed, resulting in a decrease in its rigidity, thereby reducing the mechanical properties.
[0053] Although the flame retardant grades of Examples 1 and 2 are V2 (dripping and burning cotton), their mechanical properties remain excellent. As the amount of halogen-free flame retardant increases, the flame retardant grade of Example 3 is V1 (dripping and non-burning cotton), and the flame retardant grades of Examples 4 and 5 are V0 (41S) and V0 (26S), respectively, which can improve the mechanical properties of PA6 resin while also improving its flame retardant properties. Examples 6 and 7 change the main content of nylon resin, but still maintain good flame retardant properties while maintaining excellent mechanical properties. Comparison of Example 1 and Example 4 shows that when the same number of halogen-free flame retardants are added, the flame retardant grade of Example 4 to which a phosphorus-containing bridging agent and a cross-linking agent are added is V0 (41S), while the flame retardant grade of Comparative Example 1 is V2 (dripping and burning cotton). At the same time, it can be seen from the comparison between Example 5 and Comparative Example 2 that, when the same flame retardant fraction is added, the flame retardant grade of Example 5 is V0 (26s), and the flame retardant grade of Comparative Example 2 is V0 (39s). This is attributed to the fact that the phosphorus-containing bridging agent and the cross-linking agent undergo a thermal cross-linking reaction during the combustion process. During the combustion process, the double bond reacts with the benzene ring structure in the phosphorus-containing flame retardant through thermal cross-linking to generate a rigid and stable aromatic condensed ring structure, which improves the flame retardant performance; secondly, although the flame retardant grade of Comparative Example 2 can reach V0, its mechanical properties are extremely poor. Comparative Example 1 and Comparative Example 4 can be compared to show that, under the same number of flame retardants, the dripping of Comparative Example 1 during the combustion process will cause the cotton underneath to ignite, while Comparative Example 4 does not drip. This is attributed to the fact that the phosphorus-containing bridging agent and the cross-linking agent significantly increase the melt viscosity during combustion, and promote carbonization on the surface of the dripping material, effectively preventing the dripping of PA6 during the combustion process.
[0054] From the glass fiber content test, it can be seen that the glass fiber contents of Examples 1 to 7 and Comparative Examples 1 to 6 are substantially the same, so the changes in the main mechanical properties and flame retardant properties in the present invention are caused by the changes in the amounts of the phosphorus-containing bridging agent and the cross-linking agent.
[0055] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A fluorine-free and halogen-free flame-retardant PA6 material, characterized by: Calculated by weight, the raw materials include 400-800 parts of nylon 6 resin, 10-100 parts of toughening agent, 30-300 parts of halogen-free flame retardant, 10-60 parts of phosphorus bridging agent containing benzene ring and carboxyl group, 5-15 parts of polyvinyl alcohol, 3-15 parts of other additives and 200-400 parts of glass fiber.
2. The fluorine-free and halogen-free flame-retardant PA6 material according to claim 1, characterized in that: The fluorine-free and halogen-free flame-retardant PA6 material, in parts by weight, comprises raw materials of 400-800 parts of nylon 6 resin, 10-50 parts of toughening agent, 90-250 parts of halogen-free flame retardant, 10-50 parts of phosphorus-based bridging agent containing benzene ring and carboxyl group, 5-30 parts of polyvinyl alcohol, 3-10 parts of other additives and 200-400 parts of glass fiber.
3. The fluorine-free and halogen-free flame-retardant PA6 material according to claim 1, characterized in that: The polyvinyl alcohol is polyvinyl alcohol 1799.
4. The fluorine-free and halogen-free flame-retardant PA6 material according to claim 1, characterized in that: The phosphorus-based bridging agent containing a benzene ring and a carboxyl group includes at least one of bis(4-carboxyphenyl)phenylphosphine oxide, hexa-p-carboxyphenoxy cyclotriphosphazene, [(6-oxo-6H-dibenzo[c,e][1,2]oxaphosphorin-6-yl)methyl]succinic acid, 26-oxo-6H-dibenzo(c,e)(1,2)oxaphosphorin-6-one-succinic acid (DOPOMA) or [(6-oxo-6H-dibenzo[c,e][1,2]oxaphosphorin-6-yl)methyl]succinic anhydride, 2-carboxyethylphenylphosphinic acid, and phenyldicarboxyphenylphosphine oxide.
5. The fluorine-free and halogen-free flame-retardant PA6 material according to claim 1, characterized in that: When the phosphorus-based bridging agent containing a benzene ring and a carboxyl group is [(6-oxo-6H-dibenzo[c,e][1,2]oxaphosphorin-6-yl)methyl]succinic acid, the phosphorus-based bridging agent containing a benzene ring and a carboxyl group is cross-linked with the polyvinyl alcohol to form the following product: Wherein R1, R2, R3, R4 can be [C2H4O] m The repeating unit is composed of 1, wherein m is 1 to 1800.
6. The fluorine-free and halogen-free flame-retardant PA6 material according to claim 1, characterized in that: The toughening agent includes methyl methacrylate-butadiene-styrene terpolymer and / or high-rubber powder.
7. The fluorine-free and halogen-free flame-retardant PA6 material according to claim 1, characterized in that: The halogen-free flame retardant includes aluminum hypophosphite and / or diethyl aluminum hypophosphite.
8. The fluorine-free and halogen-free flame-retardant PA6 material according to claim 1, characterized in that: The other additives include antioxidants and / or lubricants, and the antioxidants and lubricants are composed in a weight ratio of 1:1 to 3.
9. A method for preparing the fluorine-free and halogen-free flame-retardant PA6 material according to any one of claims 1 to 8, comprising the following steps: weighing the raw materials, stirring and mixing them at high speed, extruding and granulating, and cooling to obtain the fluorine-free and halogen-free flame-retardant PA6 material.
10. Use of the fluorine-free and halogen-free flame-retardant PA6 material according to any one of claims 1 to 8 in office chairs, home appliances, automobiles or power tool industries.
Citation Information
Patent Citations
Polyamide composite material and preparation method thereof
CN103408926A
High glow-wire ignition temperature halogen-free flame-retardant reinforced nylon composite and preparation method thereof
CN103602061A
Halogen-free flame-retardant glass fiber-reinforced PA6 composite material with high-ignition-temperature glow wire and high CTI value and preparation method of halogen-free flame-retardant glass fiber-reinforced PA6 composite material with high-ignition-temperature glow wire and high CTI value
CN108587145A
Wear-resistant flame-retardant lubricating coating material and preparation method thereof
CN118165589A